2010
DOI: 10.1016/j.ridd.2010.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions in individuals with intellectual disability

Abstract: 581 83 Linköping, Sweden, or henrik.danielsson@liu.se. Telephone +46 13 28 21 99 and fax +46 13 28 21 45. Executive Functions in Intellectual Disability 2 AbstractThe aim of the present study was to investigate executive functions in adults with intellectual disability, and compare them to a closely matched control group longitudinally for 5 years. In the Betula database, a group of adults with intellectual disability (ID, n=46) was defined from measures of verbal and nonverbal IQ. A control group, with two pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 24 publications
9
72
2
7
Order By: Relevance
“…Other studies have reported mental age appropriate performance on Tower tasks (Numminen, Lehto, Ruoppila, 2001). By contrast, in a recent study, no differences were found on the Tower of Hanoi or on dual tasks with retrieval demands between adults with ID and a group matched for chronological age (CA), sex, years of education and type of education (Danielsson, Henry, Rönnberg & Nilsson, 2010). Regarding executiveloaded working memory (ELWM) tasks, MA appropriate performance has been reported (Numminen et al, 2002), but see Carretti, Belacchi and Cornoldi, (2010) for an argument that difficulties in this area might be more apparent for 'high demand' ELWM tasks.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Other studies have reported mental age appropriate performance on Tower tasks (Numminen, Lehto, Ruoppila, 2001). By contrast, in a recent study, no differences were found on the Tower of Hanoi or on dual tasks with retrieval demands between adults with ID and a group matched for chronological age (CA), sex, years of education and type of education (Danielsson, Henry, Rönnberg & Nilsson, 2010). Regarding executiveloaded working memory (ELWM) tasks, MA appropriate performance has been reported (Numminen et al, 2002), but see Carretti, Belacchi and Cornoldi, (2010) for an argument that difficulties in this area might be more apparent for 'high demand' ELWM tasks.…”
Section: Introductionmentioning
confidence: 64%
“…Regarding executiveloaded working memory (ELWM) tasks, MA appropriate performance has been reported (Numminen et al, 2002), but see Carretti, Belacchi and Cornoldi, (2010) for an argument that difficulties in this area might be more apparent for 'high demand' ELWM tasks. In relation to fluency tasks and dual tasks, Danielsson et al (2010) reported lower performance for adults with ID compared to adults matched for CA and other attributes (see earlier).…”
Section: Introductionmentioning
confidence: 81%
“…In contrast, no inhibition differences were found for adults with ID versus control participants with average intelligence (Danielsson, Henry, Rönnberg, & Nilsson, 2010). In children, EF impairments comprised difficulties in cognitive flexibility (Danielsson, Henry, Messer, & Rönnberg, 2012) and working memory (Danielsson et al, 2010;Schuchardt, Gebhardt, & Mäehler, 2010). The results of other studies also show individuals with MBID to perform worse on cognitive flexibility and working memory when compared to same-aged participants with average intelligence, but not when matched with regard to mental age (Danielsson et al, 2012;Henry & MacLean, 2002).…”
Section: Efs In Children With Mbidmentioning
confidence: 83%
“…It is certainly possible that impaired working memory may be more strongly associated with externalizing behavior in children with MBID than in preschool children with externalizing behavior from the general population, simply because a minimal level of working memory is required to process social information adequately. As children with MBID tend to already perform poorly in working memory, they may not attain this minimum level (Danielsson et al, 2010;Van der Molen et al, 2007), which may lead to inadequate processing of social information and externalizing behavior problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation